The Effects of Unequal Reward Distributions on Cooperative Problem Solving by Cottontop Tamarins (Saguinus oedipus) - Cronin, Katherine A. (2008)
Cooperation among non-human animals has been the topic of much theoretical and empirical research, but few studies have examined systematically the effects of various reward payoffs on cooperative behaviour. Here, we presented heterosexual pairs of cooperatively breeding cottontop tamarins with a cooperative problem solving task. In a series of four experiments, we examined how the tamarins’ cooperative performance changed under conditions in which (a) both actors were mutually rewarded, (b) both actors were rewarded reciprocally across days, (c) both actors competed for a monopolizable reward and (d) one actor repeatedly delivered a single reward to the other actor. The tamarins demonstrated sensitivity to the reward structure, exhibiting the greatest percentage of trials solved and shortest latency to solve the task in the mutual reward experiment and the lowest percentage of trials solved and longest latency to solve the task in the experiment in which one actor was repeatedly rewarded. However, even in the experiment in which the fewest trials were solved, the tamarins still solved 46 ± 12% of trials and little to no aggression was observed among partners following inequitable reward distributions. The tamarins did, however, exhibit selfish motivation in each of the experiments. Nevertheless, in all experiments, unrewarded individuals continued to cooperate and procure rewards for their social partners.